Oxidative Stress and Apoptosis Contributed to Nonylphenol-Induced Cell Damage in Mouse NCTC Clone 1469 Cells. (26th September 2020) - Liu, Xiaozhen; Chen, Yangjie; Nie, Shaoping; Li, Fuxiang; Zhu, Zhaoliang; Peng, Gaoyi; Yu, Qiang; Xie, Mingyong
Abstract : Nonylphenol (NP) is considered an environmental toxicant and endocrine-disrupting compound. The present study aimed to investigate the effects of NP on NCTC Clone 1469, nonparenchymal hepatocytes, and to study the molecular basis of NP-induced liver injury. The results showed that NP decreased cell viability and induced nucleus crenulation and intracellular enzyme leakage in NCTC Clone 1469 cells. Additionally, NP-induced oxidative stress and apoptosis of NCTC Clone 1469 are accompanied by upregulating reactive oxygen species (ROS) production, increase of Bax, decrease of Bcl-2, activation of caspase-3 and caspase-12, and release of cytosolic free Ca 2+ in the cells. ROS scavenger, N-acetyl-L-cysteine (NAC), prevented the intracellular enzyme leakage induced by NP. NP induced alteration of estrogen receptor- (ER-) α and ER- β expression, while ER antagonists, ICI 182, 780, showed no effect on NP-induced intracellular enzyme leakage. We proposed that NP triggered cell damage via inducing oxidative stress and apoptosis in cells, but not estrogenic effect.